ANALISIS PARTISIPASI MASYARAKAT DALAM PERENCANAAN, PEMASANGAN DAN PEMELIHARAAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) DI DESA OLU KECAMATAN LINDU KABUPATEN POSO - Pirade, Yulius Salu Pirade (Katalogis, 2016)
This study aims at determining the level of public participation and the role of institutions/ organizations of local communities in planning, installating and maintaning solar power in Olu village Lindu Sigi Sub-District. The type of this research is quantitative research the analysis method is a combination of qualitative and quantitative. To obtain the data in this research, the researcher used the following data collection techniques: questionnaires, interviews, observations, and focus group discussions. The results of this study will be measured by using Likert Scale, in which in the measurement, the respondents were given several alternatives to choose one most appropriate answer considerably. The scale is used as it is able to distinguish the observed subjects based on different degrees of typical ordinate characteristics in terms of coduct symptoms. The results of this study conclude that: The calculation results of community participation in the planning stage are in Less Good category, the implementation phase of establishment is in the category of Good and the maintenance phase is in the category of Very Good. This indicates that the PLTS program in Olu village goes well. The role of local institutions in supporting the implementation of the plan, establishment and maintenance of solar power in Olu village is high enough because of the the presence of coordination among the village government, the local organizations and village institutions administrators that have a concern, attention and proactive actions on the program of PLTS construction in Olu village